The Legal Issues of Contractual Liability for the Act of the Thing “Comparative Study” - Al Dajeh, Bakhit Moh’d (Journal of Ecohumanism, 2024)
Civil liability is based on a fundamental principle that anyone who causes harm through their fault is obligated to provide compensation. The essence of this principle is that an individual is held accountable only for their personal conduct, even if it takes the form of omission, particularly within the scope of contractual liability. However, there are always exceptions to the rule. Does an individual bear responsibility for the actions of objects used in the execution or hindrance of a contract, or for causing harm to the creditor, such as tools, means, or machinery used in conjunction with contract execution? Based on this, the study seeks to explore one of the exceptional cases in contractual liability that goes beyond the scope of personal theory in its basic and general concept, namely, contractual liability for the act of the thing. Especially considering that civil legislation, for the most part, has not explicitly addressed the regulation of this liability, which has sparked controversy and discussions regarding adaptation and the determination of the responsible party and the extent of their liability. This study aims to propose logical solutions based on the realities of the available legal principles.